Self-efficacy, effort, and performance perceptions enhance psychological responses to strength training in National Collegiate Athletic Association Division I athletes - Biscardi, L. M.; Miller, A. D.; Andre, M. J.; Stroiney, D. A. (The Journal of Strength and Conditioning Research, 2024)
This study examined the effect of self-efficacy, effort, and perceived performance on positive well-being (PWB) and psychological distress (PD) following high-intensity resistance training sessions in collegiate student-athletes. An observational field study design was used to collect data before and after resistance training sessions in a 4-week preseason strength training block. A multilevel model assessed day-level and person-level variance in acute PWB and PD. Interaction terms were also tested at the day level. Alpha was set at 0.05. Within a 4-week training block, training session intensity did not predict changes in acute psychological responses. After controlling for an athlete's preexercise psychological state, higher self-efficacy, daily effort, and perceived performance predicted higher PWB and lower PD following training (p < 0.05). Self-efficacy moderated the relationships of daily effort and performance with PD (p < 0.05). When athletes experienced lower self-efficacy, producing a higher effort and perceiving better performance reduced the negative psychological response. These findings highlight the important mediating role of cognitive variables in the acute psychological response to high-intensity resistance training. Coaches should identify and mitigate low cognitive states to facilitate a positive psychological response to resistance training. This strategy promotes a positive psychological response without altering training prescription.